النظام القانوني للمناطق الحرة في التشريع الجزائري - زرود, عبد الرحمان (University of Eloued جامعة الوادي, 2023)
تسعى الجزائر في السنوات الأخيرة للتنويع من إيراداتها من خلال دعم وتشجيع الإستثمار بحيث سعت السلطات لإستقطاب المستثمرين الأجانب وتشجيع المستثمرين المحليين وهذا بهدف تنويع وتطوير الإقتصاد الوطني بالإستثمار خارج قطاع المحروقات عن طريق تقديم العديد من الإمتيازات المحفزة لتجسيد المشاريع وبعث النشاطات الإستثمارية المتنوعة التي تتطلب توفير الحافظة العقارية المناسبة، بحيث وفرت الدولة العديد من أصناف العقار الصناعي بإستثناء المناطق الحرة، والتي تسعى لإعادة إنشائها كما منحتها العديد من الامتيازات المغرية التي يتحصل عليها المستثمرين من خلال إنجازهم لنشاطاتهم بالمنطقة الحرة، وذلك لما تحضى به من منضومة قانونية خاصة، ومن خلال هذا سنتطرق لكل من( مفهومها، أنواعها، تصنيفها، منح إستغلالها طرق حل نزاعاتها) كما تساهم المناطق الحرة بتحقيق العديد من الأهداف للدول المضيفة، كنقل التكنولوجيا الحديثة إليها.In recent years, Algeria has been seeking to diversify its revenues by supporting and encouraging investment.The authorities sought to attract foreign investors and encourage local investors with the aim of diversifying and developing the national economy, by investing outside the hydrocarbon sector by providing many stimulating privileges to embody projects and launch various investment activities that require the provision of an appropriate real estate.That was by providing many types of industrial real estate, with the exception of free zones, which it seeks to be re-established.And also by granting many attractive privileges that investors could obtain through carrying out their activities in the free zones, because of its special legal system.Through all this, we will address each of (its concept, types, classification, granting of its exploitation, methods of resolving its disputes). And also the free zones contribute to achieving many objectives for the country, such as transferring modern technology to it.
مذكرة ماستر
Keywords: : الإستثمار – العقار الصناعي – المناطق الحرة- منح الإمتياز: investment - industrial real estate - free zones - franchising